The neuroplastin adhesion molecules are accessory proteins that chaperone the monocarboxylate transporter MCT2 to the neuronal cell surface. - Marieangela C Wilson (Public Library of Science (PLoS), 2013)
Background The neuroplastins np65 and np55 are two synapse-enriched immunoglobulin (Ig) superfamily adhesion molecules that contain 3 and 2 Ig domains respectively. Np65 is implicated in long term, activity dependent synaptic plasticity, including LTP. Np65 regulates the surface expression of GluR1 receptor subunits and the localisation of GABA(A) receptor subtypes in hippocampal neurones. The brain is dependent not only on glucose but on monocarboxylates as sources of energy. The. monocarboxylate transporters (MCTs) 1-4 are responsible for the rapid proton-linked translocation of monocarboxylates including pyruvate and lactate across the plasma membrane and require association with either embigin or basigin, proteins closely related to neuroplastin, for plasma membrane expression and activity. MCT2 plays a key role in providing lactate as an energy source to neurons. Methodology/findings Here we use co-transfection of neuroplastins and monocarboxylate transporters into COS-7 cells to demonstrate that neuroplastins can act as ancillary proteins for MCT2. We also show that Xenopus laevis oocytes contain endogenous neuroplastin and its knockdown with antisense RNA reduces the surface expression of MCT2 and associated lactate transport. Immunocytochemical studies show that MCT2 and the neuroplastins are co-localised in rat cerebellum. Strikingly neuroplastin and MCT2 are enriched in the same parasagittal zebrin II-negative stripes. Conclusions These data strongly suggest that neuroplastins act as key ancillary proteins for MCT2 cell surface localisation and activity in some neuronal populations, thus playing an important role in facilitating the uptake of lactate for use as a respiratory fuel.